Effect of Adding Methionine or Choline Chloride to the Low Protein Diets During Production Period of Japanese Quail - Jalal, Fatma Mustafa; AL-Neemi, Mohammad Ibrahim (Sulaimani Journal for Pure and Applied Sciences, 2018)
The experiment was conducted in the farm of Poultry - Animal Production department of the faculty of Agriculture - University of Kirkuk from the period of 28.12.2016 until 25.2.2017. The aim of this experiment was to determine the effect of adding Methionine and Choline Chloride more than the NRC recommended to the low protein diets on production phase of Japanese Quail. Distributed randomly 140 female Japanese Quail (65 days old) to7 treatments 20 birds each, in five replicates containing 4 birds each cage with dimensions 40×30×20 cm as replicate. Birds fed dietary treatment: control (20% crude protein), T1(18% crude protein), T2(16% crude protein), T3(18% crude protein + adding 20% more than the nutritional requirement of methionine), T4(16% crude protein + adding 20% more than the nutritional requirement of methionine), T5(18% crude protein + adding 20% more than the nutritional requirement of choline) and T6(16% crude protein + adding 20% more than the nutritional requirement of choline) . The statistical analysis obtained no significant differences in egg production (H.D %), egg mass, egg weight, feed intake, feed conversion ratio, energy intake and energy conversion ratio. While significant differences have obtained in the mean conversion ratio of protein, methionine and choline, the T1 (control) was significantly (p<0.05) higher than all other treatments in mean of protein intake. The T4 and T5 were significantly higher than all other treatments in the methionine intake. The T6 and T7 were significantly higher than all other treatments in choline intake. The T5 was the beast treatment in protein conversion ratio among treatments, there was significant improvement in mean of methionine conversion ratio in all treatments except T4 and T5. There was significant improvement in mean of choline conversion ratio in all treatments except T6 and T7. The T2 was significantly higher than T6 in mean of shape index and egg specific gravity. The results showed higher shell thickness significantly in (T1) and (T2) treatment compared to other treatment. The T2 and T7 significantly higher than T6 in the percentage of egg shell. The T1 and T4 significantly higher than T7 in The mean of yolk index. The T4 was significantly higher than T7 in mean of yolk percentage and there was no significant differences found in the mean albumen weight percentage, albumen index and haugh unit.
Keywords: Methionine; Choline Chloride; low protein diets; Japanese Quail